Dinoflagellate Host Chloroplasts and Mitochondria Remain Functional During Amoebophrya Infection - Kayal, Ehsan; Alves-de-Souza, Catharina; Farhat, Sarah; Velo-Suarez, Lourdes; Monjol, Joanne; Szymczak, Jeremy; Bigeard, Estelle; Marie, Dominique; Noel, Benjamin; Porcel, Betina M.; Corre, Erwan; Six, Christophe; et al. (Frontiers in Microbiology, 2020)
Dinoflagellates are major components of phytoplankton that play critical roles in many microbial food webs, many of them being hosts of countless intracellular parasites. The phototrophic dinoflagellate Scrippsiella acuminata (Dinophyceae) can be infected by the microeukaryotic parasitoids Amoebophrya spp. (Syndiniales), some of which primarily target and digest the host nucleus. Early digestion of the nucleus at the beginning of the infection is expected to greatly impact the host metabolism, inducing the knockout of the organellar machineries that highly depend upon nuclear gene expression, such as the mitochondrial OXPHOS pathway and the plastid photosynthetic carbon fixation. However, previous studies have reported that chloroplasts remain functional in swimming host cells infected by Amoebophrya. We report here a multi-approach monitoring study of S. acuminata organelles over a complete infection cycle by nucleus-targeting Amoebophrya sp. strain A120. Our results show sustained and efficient photosystem II activity as a hallmark of functional chloroplast throughout the infection period despite the complete digestion of the host nucleus. We also report the importance played by light on parasite production, i.e., the amount of host biomass converted to parasite infective propagules. Using a differential gene expression analysis, we observed an apparent increase of all three mitochondrial and nine out of the eleven plastidial genes involved in the ETC of the respiration pathways during the first stages of the infection. The longer resilience of organellar genes compared to those encoded by the nucleus suggests that both mitochondria and chloroplasts remain functional throughout most of the infection. This extended organelle functionality, along with higher parasite production under light conditions, suggests that host bioenergetic organelles likely benefit the parasite Amoebophrya sp. A120 and improve its fitness during the intracellular infective stage.